Encouraging, restricting, or preventing: alternative models of immigration policy making in Taiwan - Jent, An-Lin; Soong, Jenn-Jaw (Penerbit UKM, 2012)
Globalization has not only accelerated international migration, but has also been a dynamic force for change in national political economies. Rapid economic growth in East Asia has led to great demand for immigrant labor for example, yet many states in East Asia have adopted strict controls on international labor migration. Due to international needs and domestic conditions however, these states cannot avoid an influx of migration. Taiwan is one of Asia’s four` little dragons, but it faces developmental limitations due to its small land mass. In recent years, faced with a rapidly changing social structure and the urgent need for economic transformation, many more migrants are arriving from Southeast Asia and Mainland China. What are the main factors behind this? This article will focus on the functional imperatives of the Taiwanese state in respect to migration, and will explore the crucial pull factors involved in migration to Taiwan, from demographics, economic needs and national efficiency, to civil society. Furthermore, it will develop a dynamic model that can help explain and predict the shape of immigration policy in terms of encouragement, restriction, or the prevention of new settlers.